Two-stage S-band erbium-doped fiber amplifier using a depressed-cladding fiber - Harun, S. W.; Saat, N. K.; Ahmad, H. (2005)
A two-stage short-wavelength-band erbium-doped fiber amplifier (S-band EDFA) is demonstrated using a depressed-cladding erbium-doped fiber (EDF). The EDF has a fundamental-mode cutoff wavelength of about 1525 nm in order to suppress amplified spontaneous emission at the longer wavelength. The highest gain curve is obtained by setting the first- and second-stage pumps at 85 and 190 mW, respectively, where the unsaturated gains are obtained at about 28 dB. The gain was limited by the 12-dBm saturation power of the amplifier. The unsaturated noise figure ranged from 8.5 to 9.3 dB for all pump combinations tested. (c) 2005 Wiley Periodicals. Inc.